Girls gone wise in a world gone wild - Kassian, Mary A. (Chicago : Moody Publishers, 2010)
Mary Kassian walks the reader through the compelling tale of the wild versus wise woman found in Proverbs 7. By using 21 points of contrast, the reader will be able to discern the difference between wild and wise. --from publisher description
Heart -- Counsel -- Approach -- Attitude -- Habits -- Focus -- Appearance -- Body language -- Roles -- Sexual conduct -- Boundaries -- Authenticity -- Neediness -- Possessions -- Entitlement -- Reliability -- Speech -- Influence -- Sustainability -- Teachability.
Includes bibliographical references (p. [269]-272).
Keywords: Christian women -- Religious life